PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PKN DI KELAS VII-3 SMP NEGERI 1 NAMORAMBE TAHUN AJARAN 2018/2019 - Tarigan, Latifah Hanum (JGK (Jurnal Guru Kita), 2022)
Abstract: Application of the Contextual Teaching and Learning Model to Improve Student Motivation in Civics Subjects in Class Vii-3 SMP Negeri 1 Namorambe Academic Year 2018/2019. This study aims to determine the increase in students' learning motivation by using the Contextual Teaching and Learning learning model in Class VII-3 SMP Negeri 1 Namorambe in the 2018/2019 academic year. The research method is in the form of classroom action research and the research subject is Class VII-3. The class studied consisted of 34 students. Based on the learning outcomes from the first cycle, the average score was 75. After the second cycle, there was an increase to 85. In this study, the data obtained for individual and classical learning completeness criteria were 34 students or 100%. Thus the learning in this research can be said to have been completed. The level of student mastery of the material being taught, which is made based on the final test is 100% of students who have very high mastery. Based on the results of the research above, it can be concluded that learning using the Contextual Teaching And Learning learning model in Class VII-3 SMP Negeri 1 Namorambe T.P. 2018/2019 experienced an increase in student learning motivation.PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PKN DI KELAS VII-3 SMP NEGERI 1 NAMORAMBE TAHUN AJARAN 2018/2019
Keywords: Keywords Learning Motivation; Contextual Teaching and Learning.